RESEARCHING OF THE LAWS OF FORMATION OF HIGH-STRENGTH ANTIBURNING COATINGS, MODIFIED BY NANOSTRUCTURED MATERIALS - J. A. Nikolaichik (Литьë и металлургия)
The influence of the nanostructured modifier quantity on high-strength antipenetration coatings is analyzed and optimum range of its concentration (4,5%) is set.